DINAMIKA LEMBAGA DEMOKRASI DESA DI INDONESIA (Sebuah Kajian Pustaka): sebuah kajian pustaka - Muhammad Saleh (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2021)
The purpose of this study is to elaborate on the development of rural democratic practices in Indonesia. In the development of democratic practices in villages, there have been ups and downs recently as a result of the concept of government institutionalized by the government above it or supra village. This resulted in the loss of the main characteristics possessed by the village. The main characteristics referred to are the loss of local wisdom, mutual cooperation, and even the character of individualism has begun to penetrate the joints of village community life. This study uses literature study by parsing various theories, opinions across history both during the old order, the new order, up to the current reform era to get a comprehensive picture. The results of the study found that there are ups and downs of democratic practices in Indonesia which are caused by the implementation of the concept of a state from the regime that is currently in power. The ups and downs can be seen in the tug-of-war in village democratic institutions represented by the executive, namely the village head and the legislative body, namely the village consultative body (Law Number 5 of 1979, Law Number 22 of 1999, Law Number 32 of 2004, and Law Number 6 of 2014).  Keywords: democracy, village, local wisdom, local institutions   ABSTRAK Penelitian bertujuan ini adalah untuk melakukan elaborasi tentang perkembangan praktek demokrasi desa di Indonesia.  Dalam perkembangan praktek demokrasi di desa akhir-akhir ini terjadi pasang surut sebagai akibat dari konsep pemerintahan yang dilembagakan oleh pemerintah di atasnya atau supra desa.  Ini mengakibatkan hilangnya karakteristik utama yang dimiliki oleh desa. Karakterisitik utama dimaksud adalah hilangnya kearifan lokal/local wisdom, gotong royong, bahkan watak individualisme mulai merasuki sendi kehidupan masyarakat desa.  Studi ini menggunakan studi pustaka dengan mengurai berbagai teori, pendapat lintas sejarah baik pada masa orde lama, orde baru, sampai dengan pada masa reformasi saat ini untuk mendapatkan gambaran yang komprehensif.  Hasil penelitian ditemukan adanya pasang surut praktek demokrasi di Indonesia yang disebabkan oleh pelaksanaan konsep bernegara dari rezim yang sedang berkuasa.  Pasang surut ini dapat dilihat terjadi tarik ulur pada lembaga demokrasi desa yang diwakili oleh lembaga eksekutif yaitu kepala desa dan lembaga legislatif yaitu lembaga permusyawaratan desa (Undang-Undang Nomor 5 tahun 1979, Undang-Undang Nomor 22 Tahun 1999, Undang-Undang Nomor 32 tahun 2004 dan UU Nomor 6 Tahun 2014). Kata kunci: demokrasi, desa, kearifal lokal, institusi lokal